Operational Impacts of the Changes in the Corn Futures Contract of the BM&F Bovespa Regarding Risk Mitigation - Souza, Waldemar Antonio da Rocha de; Guerra, Fabio Bandeira; Zanin, Vanclei; Martines Filho, João Gomes (Review of Business Management, 2012)
The corn market plays an important role in the national agricultural scenario, given its relevance in the meat industry, where grain marketing strategies are outstanding, especially those related to price risk mitigation using futures contracts. This article aims to identify and interpret the effects of the changes of the corn futures contract traded at the BM&F-Bovespa, which shifted in September 2008 from physical delivery to cash settlement, on the grain futures market performance. We evaluated contract liquidity, volatility of future and physical corn prices, and base convergence. The possible effects of the contract amendment include the increase in liquidity of the corn futures contract, reduction of the price volatility and improved base convergence. The results are in line with the theory and highlight the positive impact of implementing cash settlement for corn futures. Key words: Cash settlement. Futures contracts. Corn. BM&F-Bovespa.